CCAFS engagement has fostered ongoing investment in climate services of nearly 3M in LAM with 10M additional in the pipeline. - CGIAR Research Program on Climate Change, Agriculture and Food Security (2017)
The CCAFS AgroClimas project and its associated bilateral agreements have been the first major push for capacity building and development of shared expertise in agro-climate services at the regional scale, spanning Colombia, Peru, and Central America. This included the Local Technical Agro-climatic Committees (LTACs), PICSA, integrated co-production processes, automated data workflows, and standardized tools and methods. The result has been institutional buy-in for CS, concomitant investment of USD ~2.8M in LAM, and an additional USD 10M in the pipeline.